Valorization of bamboo shoot shell waste for the coproduction of fermentable sugars and xylooligosaccharides - Wang, Qiyao; Su, Yan; Gu, Yang; Lai, Chenhuan; Ling, Zhe; Yong, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, hydrothermal pretreatment (autohydrolysis) was coupled with endo-xylanase enzymatic hydrolysis for bamboo shoot shell (BSS) to produce glucose and valuable xylooligosaccharides (XOS) rich in xylobiose (X2) and xylotriose (X3). Results showed that the enzymatic hydrolysis efficiency of pretreated BSS residue reached 88.4% with addition of PEG during the hydrolysis process. To enrich the portions of X2–X3 in XOS, endo-xylanase was used to hydrolyze the XOS in the prehydrolysate, which was obtained at the optimum condition (170°C, 50 min). After enzymatic hydrolysis, the yield of XOS reached 25.6%, which contained 76.7% of X2–X3. Moreover, the prehydrolysate contained a low concentration of fermentation inhibitors (formic acid 0.7 g/L, acetic acid 2.6 g/L, furfural 0.7 g/L). Based on mass balance, 32.1 g of glucose and 6.6 g of XOS (containing 5.1 g of X2-X3) could be produced from 100.0 g of BSS by the coupled technology. These results indicate that BSS could be an economical feedstock for the production of glucose and XOS.